Diesel-storage hybrid independent micro-grid dynamic frequency stabilization strategy based on virtual synchronous generator - HU CHAO; ZHANG XING; XU HAIZHEN; SHI RONGLIANG; LI MING; LIU FANG; GU JUN (2016)
For the problems of rapid change of system frequency and slow recovery speed of a system frequency caused by small inertia and slow dynamic response speed of a diesel generating set in a diesel-storage hybrid independent micro-grid system, the invention discloses a diesel-storage hybrid independent micro-grid dynamic frequency stabilization strategy based on a virtual synchronous generator. The diesel-storage hybrid independent micro-grid dynamic frequency stabilization strategy comprises a virtual synchronous generator control method which can provide inertia and damping support for a diesel-storage hybrid independent micro-grid and can also provide dynamic power compensation. When the diesel-storage hybrid independent micro-grid system is subject to load disturbance, the amplitude deviation of the system frequency can be reduced, and the overshooting of the system frequency in a recovery process can be inhibited to guarantee the rapid recovery of the system frequency, thereby effectively improving the power